Properties of a New Fourier Transform-based Steganographic Method - Harbarchuk, V.; Koziel, G. (Штучний інтелект, 2010)
￼A new Fourier transform-based steganographic method is proposed. The practical verification of properties of the presented algorithm is analyzed and discussed. The analysis of algorithm robustness to the damage of ￼the hidden information is also conducted. ￼Запропоновано новий стеганографічний метод на основі модифікації перетворення Фур’є. Практична ￼реалізація і тестування алгоритмів на основі цього методу показали його високу ефективність. ￼Предложен новый стеганографический метод на основе модификации преобразования Фурье. Практическая реализация и тестирование алгоритмов на основе этого метода показали его высокую эффективность.